Stable Isotope Analysis of Human and Faunal Remains from Rosheim, Middle Neolithic, France - Christina Cheung; Fanny Chenal; Magali Fabre; Marie Horviller; Estelle Herrscher; Aline Thomas (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The Middle Neolithic cemetery at Rosheim “Rosenmeer” (RR) (Bas-Rhin, France) contains the largest Grossgartach skeletal assemblage (first half of the 5th millennium BC) in Alsace. Rosheim is a key site to help understand the westward movement of neolithisation from the Danubian region towards Western Europe. This study presents original stable isotope analyses of carbon, nitrogen and sulfur from 61 humans from RR and 37 fauna from neighbouring contemporaneous sites. Previously published stable isotope data (19 humans and 7 fauna) from Rosheim are incorporated in the discussion. In addition to stable isotope data, biological information (i.e., age and sex) and archaeological information (i.e., temporal phases and quantity of grave goods) are also included. Consequently, this study presents a comprehensive analysis of diets and social organisation at RR, involving data from over half of the total exhumed individuals from RR. No statistically significant intra-population dietary pattern can be observed at the site, suggesting that the RR inhabitants had a rather homogenous diet for both sexes and across age groups, social stratigraphy and temporal phases. A closer inspection of juvenile isotopic compositions suggests that weaning was completed at around two years old. Faunal isotope data suggest different husbandry practices for herbivores and omnivores, respectively. Through a comparison of stable isotope compositions of human and faunal remains from the Rhine Basin with those from the contemporary Paris Basin (Cerny culture), this study demonstrates that while there are many similarities in terms of burial rites between RR and Cerny, the RR inhabitants had a more agrarian lifestyle.